Calling on Male Allies to Promote Gender Equity in I-O Psychology. Issue 3 (20th September 2018) - Cheng, Shannon; Ng, Linnea; Trump-Steele, Rachel C. E.; Corrington, Abby; Hebl, Mikki
Abstract : As Gardner, Ryan, and Snoeyink (2018 ) state, their findings on gender representation in industrial and organizational (I-O) psychology indicate that "the profession as a whole falls into the category of 'not walking the talk'" (p. 385). We agree that it is imperative to understand the current state of gender inequity in our field while also actively working toward achieving gender equity. This article attempts to inspire each and every individual in I-O psychology to feel a personal responsibility to engage in behaviors that reduce gender disparities in our field. Although women are normatively the focus in fights for gender equity, men should be equal partners in these efforts. In this commentary, we focus on the contributions that male allies in I-O psychology can make in fostering gender equity. To be clear, we are not claiming that women need to be rescued by men; however, we do believe that I-O psychology can achieve the greatest progress toward gender equity when both women and men engage in supportive efforts. As Emma Watson said in her 2014 United Nations speech, "How can we affect change in the world when only half of it is invited or feel welcome to participate in the conversation?" (UN Women, 2014 ). In times when political leaders and national laws may fail women, it is crucial that local communities—like the I-O community—adopt a clear stance in promoting gender equity. In this commentary, we define allyship, discuss the importance of male allies, suggest ways in which male allies can help promote gender equity in I-O psychology, and consider potential barriers to male allyship and ways to overcome them. The strategies that we propose are by no means exhaustive; rather, they are suggestions for how to initiate a larger movement.